(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
Environmental catastrophes, perpetuated by the unsustainable and unrestricted consumption of resources, are becoming increasingly apparent. Although elite practices often account for a disproportionate amount of resource usage, wealthy ways of life remain unchallenged while the non-elite continuously adapt to ecological crises. The cases of celebrity lawn-watering and golf course maintenance in drought-prone California represent the larger issue of elite practices that effectively oppose healthy change. These elite landscapes have become thoroughly ingrained in American culture, and dismantling their constructed necessity requires scepticism of information produced by those within dominant social orders. This paper will highlight the negative impacts of elite ecological practices while asserting that new ways of living, such as wild gardening and the repurposing of golf course land, should be embraced and empowered. Unnatural landscape aesthetics must be devalued to adapt to environmental changes, and to accomplish this feat, a cultural shift is crucial.